Being a Slave Histories and Legacies of European Slavery in the Indian Ocean - Schrikker, Alicia; Wickramasinghe, Nira (Leiden University Press, 2020)
This multidisciplinary volume brings together scholars and writers who try to come to terms with the histories and legacies of European slavery in the Indian Ocean. The volume discusses a variety of qualitative data on the experience of being a slave in order to recover ordinary lives and, crucially, to place this experience in its Asian local context. Building on the rich scholarship on the slave trade, this volume offers a unique perspective that embraces the origin and afterlife of enslavement as well as the imaginaries and representations of slaves rather than the trade in slaves itself.